2014
DOI: 10.1128/jvi.00635-14
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Hepatitis B Virus Polymerase rtA181T Mutation on Replication and Drug Resistance Is Potentially Affected by Overlapping Changes in Surface Gene

Abstract: The emergence of drug-resistant hepatitis B virus (HBV) is a major problem for antiviral treatment in chronic hepatitis B infection. In this study, we analyzed the evolution of drug-resistant mutations and characterized the effects of the rtA181T and rtI233V mutations on viral replication and drug resistance. We performed a clonal analysis of the HBV polymerase gene from serum samples during viral breakthrough treated with antiviral agents. A series of mutant clones containing rtA181T and/or rtI233V mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 38 publications
5
33
0
Order By: Relevance
“…This mutation has been reported to enhance the replication efficiency and to be associated with enhanced replication efficiency when combined with the rtM204I mutation, although rtL269I alone did not alter susceptibilities to NAs 25, 27. In our experiment, rtL269I but not rtN238H could enhance ETV resistance when combined with rtL180Q/M204V, which is consistent with previous data 27, 28…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This mutation has been reported to enhance the replication efficiency and to be associated with enhanced replication efficiency when combined with the rtM204I mutation, although rtL269I alone did not alter susceptibilities to NAs 25, 27. In our experiment, rtL269I but not rtN238H could enhance ETV resistance when combined with rtL180Q/M204V, which is consistent with previous data 27, 28…”
Section: Discussionsupporting
confidence: 92%
“…rtA181T mutation‐associated ADV resistance has been reported 28, 32, 33, 34. This mutation is often associated with a stop codon at the overlapping surface gene, and the sW172stop mutation impairs HBsAg secretion by generating a truncated protein and also causes the susceptibility to ADV to deteriorate.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of rtA181T/sW172 * multi-drug resistant mutants by widespread treatment with NAs has raised many concerns due to decreased HBV susceptibility to LMV, LdT, ADV, and tenofovir (8,10,20). Its dominant negative effect on wild-type HBV virion secretion and oncogenic potential through transactivation activities were also reported (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth to mention that the viral replication changes of this mutant are inconsistent in different in vitro cell studies. For example, the result reported by Dr.Hiromi Yatsuji showed that there was no noticeable difference in replication ability between the rtA181T/sW172* and rtA181T/sW172L12; while other two in vitro studies reported a reduced replication of rtA181T/sW172* mutant1314. Thus, to better and fully understand the characteristics of the HBV rtA181T mutant, we designed this study to investigate the impact of different overlapping S gene mutation (sW172L and sW172*) on rtA181T mutant DNA replication and viral protein expression, not only in vitro in cultured HepG2 cells but also in vivo in mouse model.…”
mentioning
confidence: 98%